Comparison of the protective effect of cytosolic and mitochondrial Peroxiredoxin 5 against glutamate-induced neuronal cell death. (1st January 2021) - Kim, Mi Hye; Kim, Da Yeon; Lee, Hong Jun; Park, Young-Ho; Huh, Jae-Won; Lee, Dong-Seok
ABSTRACT: Objectives : Although glutamate is an essential factor in the neuronal system, excess glutamate can produce excitotoxicity. We previously reported that Peroxiredoxin 5 (Prx5) protects neuronal cells from glutamate toxicity via its antioxidant effects. However, it is unclear whether cytosolic or mitochondrial Prx5 provides greater neuroprotection. Here, we investigated differences in the neuroprotective effects of cytosolic and mitochondrial Prx5. Methods : We analyzed patterns of cytosolic and mitochondrial H2 O2 generation in glutamate toxicity using HyPer protein. And then, we confirmed the change of intracellular ROS level and apoptosis with respective methods. The mitochondrial dynamics was assessed with confocal microscope imaging and western blotting. Results : We found that the level of mitochondrial H2 O2 greatly increased compared to cytosolic H2 O2 and it affected cytosolic H2 O2 generation after glutamate treatment. In addition, we confirmed that mitochondrial Prx5 provides more effective neuroprotection than cytosolic Prx5. Discussion : Overall, our study reveals the mechanisms of cytosolic and mitochondrial ROS in glutamate toxicity. Our findings suggest that mitochondrial ROS and Prx5 are attractive therapeutic targets and that controlling these factors be useful for the prevention of neurodegenerative diseases.